Strategi Pemberdayaan Ekonomi Masyarakat Melalui Budidaya Black Soldier Fly Sebagai Optimalisasi Biokonversi Limbah Organik Di Desa Sumberwaru, Jember - Devina Cinantya Anindita; Setyo Andi Nugroho; Rizky Nirmala Kusumaningtyas; Dian Galuh Pratita; Arinda Linorika S (LKP KARYA PRIMA KURSUS, 2025)
Waste remains a complex environmental issue in Indonesia. Waste is defined as the final by-product of human activities in solid or semi-solid form that is no longer utilized. In 2024, Indonesia generated approximately 35 million tons of waste, with 61.37% remaining unmanaged. The majority of this waste consists of food residues. This community service program aimed to enhance public knowledge and skills in managing food waste for the cultivation of maggot (Hermetia illucens) and its utilization as an environmentally friendly alternative feed source. The main problem faced by the community partner was the suboptimal management of household organic waste, which became the foundation for this educational program. The implementation methods included socialization, technical training on maggot cultivation, demonstration of organic waste processing as maggot media, and mentoring at the household level. The results showed a significant increase of 88% in participants’ understanding of maggot cultivation and its ecological benefits. Furthermore, participants successfully produced maggots independently for use as fish and poultry feed. This activity had a positive impact by reducing organic waste volume, lowering feed costs, and increasing environmental awareness within the community. Therefore, maggot cultivation education proved effective in supporting community-based organic waste management while simultaneously creating new economic value from previously unutilized waste.